2009
DOI: 10.1111/j.1540-4781.2009.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Other‐Repetition as a Resource for Participation in the Activity of Playing a Video Game

Abstract: This article offers an empirically based contribution to the growing body of studies using Conversation Analysis (CA) as a tool for analyzing second/foreign language learning in and through interaction. Building on a sociointeractional view of learning as grounded in the structures of participation in social activities, we apply CA methods to examine the affordances offered by interaction during the activity of playing a video game for additional language learning. We focus on one type of interactional practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…For example, in a Finnish study, Piirainen-Marsh and Tainio (2009) examined two boys in their lower teens who played a game called Final Fantasy X. Again, the findings were very positive with regard to English skills.…”
Section: Gaming and Young Language Learnersmentioning
confidence: 99%
“…For example, in a Finnish study, Piirainen-Marsh and Tainio (2009) examined two boys in their lower teens who played a game called Final Fantasy X. Again, the findings were very positive with regard to English skills.…”
Section: Gaming and Young Language Learnersmentioning
confidence: 99%
“…If a word is retrieved from memory for subsequent use, it is more likely to be remembered later in time. Repetition, for example, is an effective activity in promoting retrieval (Nation, 2001) and understanding events in a DVG (Marsh & Tainio, 2009). Creative or generative use is utilizing learned vocabulary in different contexts/ways.…”
Section: Vocabulary Acquisitionmentioning
confidence: 99%
“…Recently, there have been several studies on self-access in which young learners (ranging in age from ten to fourteen years old) demonstrated academic improvement in English from having played online multi-player video games outside of school (Jeon, 2014;Piirainen-Marsh & Tainio, 2009;Sundqvist, 2015;Sundqvist & Sylvén, 2014). Sundqvist and Sylvén (2014) found that Swedish learners of English demonstrated improvement in speaking and vocabulary through out-of-school gaming.…”
Section: Self-access Through Gaming and Other Mediamentioning
confidence: 99%